Impact of SARS-CoV-2 Infection on Erythropoietin Resistance Index in Hemodialysis Patients - Guido Gembillo; Luca Soraci; Luigi Peritore; Rossella Siligato; Vincenzo Labbozzetta; Alfio Edoardo Giuffrida; Felicia Cuzzola; Claudia Spinella; Adolfo Romeo; Vincenzo Calabrese; Alberto Montesanto; Andrea Corsonello; et al. (Geriatrics)
Background/Objectives: Hemodialysis (HD) patients with advanced chronic kidney disease (CKD) are highly vulnerable to complications from SARS-CoV-2 infection. Anemia management in this population is complex, particularly due to erythropoietin resistance, which may be exacerbated by COVID-19-related inflammation. To this aim, in this small-scale retrospective study, we investigated trends in the erythropoietin resistance index (ERI) over time in patients with and without SARS-CoV-2 infection. Methods: This single-center retrospective study included 25 HD patients, divided into two groups: 15 with a history of SARS-CoV-2 infection (CoV2 group) and 10 without (nonCoV2 group). The ERI was assessed over four visits, with 70–100-day intervals between them. Linear mixed models were used to evaluate factors associated with ERI changes. Results: Patients in the CoV2 group exhibited significantly higher ERI increases between T1 (baseline) and T2 (post-infection) compared to the nonCoV2 group (median ΔERI: +4.65 vs. −0.27, p < 0.001). During the T2–T4 recovery period, CoV2 patients demonstrated a delayed but substantial decline in the ERI, converging to baseline levels by T4. Male sex and hemoglobin levels were negatively associated with the ERI. Conclusions: SARS-CoV-2 infection induces transient but significant erythropoietin resistance in HD patients, likely due to inflammation and disrupted erythropoiesis. Tailored anemia management strategies, including the potential use of hypoxia-inducible factor stabilizers, are warranted. Larger, multicenter studies are needed to validate these findings and improve treatment protocols.